Antifungal potential of Brazilian green and brown propolis against clinically relevant yeasts - Reis, Túlio Custódio [UNESP]; Paiva, Luiz Francisley de; Costa, F. E. C.; Gonçalves, Carolina Passarelli (Brazilian Journal of Biology, 2025)
Brazilian biodiversity is rich in compounds with biological potential. Propolis is a natural product formed from bee saliva and plant exudates. Brazilian brown and green propolis exhibit antioxidant, antibacterial, antifungal, antiviral, and antiparasitic activities. These properties arise from their rich phenolic content; molecules such as artepellin-C, quercetin, and kaempferol are important phenolic biomolecules described in propolis. The objective of this study was to determine the antifungal activity and chemical parameters of brown and green propolis samples commercialized in Santa Rita do Sapucaí, southern Minas Gerais, Brazil. The total phenolic compound content was assessed using the Folin-Ciocalteu colorimetric method. Total flavonoid concentration was determined by the aluminum chloride complexation method. The pH and density were also determined. The antifungal activity of the extracts was evaluated using the disk diffusion technique against strains from the American Type Culture Collection (ATCC), following the Kirby-Bauer methodology. Both extracts showed similar densities; the green propolis extract presented a pH of 4.37, while the brown propolis extract showed a pH of 3.61. The ethanolic extract of brown propolis (706.79 mg GAE/g) exhibited a higher content of phenolic compounds compared to green propolis (697.65 mg GAE/g), whereas the green propolis extract (415.75 mg QE/g) presented a higher flavonoid content than brown propolis (378.75 mg QE/g). Clinically relevant strains, Candida albicans (EPM: 12.43 mm; EPV: 12.78 mm), Candida parapsilosis (EPM: 14.88 mm; EPV: 13.96 mm), and Cutaneotrichosporon dermatis (EPM: 11.95 mm; EPV: 12.28 mm), were the most susceptible to both extracts. It can be inferred that the extracts possess excellent antifungal activity, possibly associated with their rich phenolic and flavonoid content.

Potencial antifúngico das própolis verde e marrom brasileiras contra leveduras clinicamente relevantes. A própolis é um produto natural formado a partir da saliva de abelhas e exsudatos vegetais. A biodiversidade brasileira é rica em compostos com potencial biológico. A própolis marrom e verde brasileira apresentam atividade antioxidante, antibacteriana, antifúngica, antiviral e antiparasitária. Essas propriedades são oriundas de seu rico conteúdo fenólico, moléculas como o artepellin-C, a quercetina e o kaempferol são importantes biomoléculas fenólicas descritas para a própolis. O objetivo deste trabalho foi determinar a atividade antifúngica e parâmetros químicos de amostras de própolis marrom e verde comercializados em Santa Rita do Sapucaí, sul de Minas Gerais, Brasil. O teor de compostos fenólicos totais foi avaliado utilizando o método colorimétrico de Folin-Ciocalteau. A concentração de flavonoides totais foi determinada pelo método de complexação com cloreto de alumínio. O pH e a densidade também foram determinados. A atividade antifúngica dos extratos foi avaliada através da técnica de disco-difusão frente a cepas da American Type Culture Collection (ATCC) seguindo a metodologia de Kirby-Bauer. Ambos os extratos apresentaram densidades similares, o extrato de própolis verde apresentou pH referente a 4.37, enquanto o extrato de própolis marrom apresentou pH referente a 3.61. O extrato etanólico de própolis marrom (706,79 mg EAG/g) apresentou maior conteúdo de compostos fenólicos se comparado ao de própolis verde (697,65 mg EAG/g), enquanto o extrato de própolis verde (415,75 mg EQ/g) apresentou maior conteúdo de flavonoides se comparado a própolis marrom (378,75 mg EQ/g). As cepas de relevância clínica, Candida albicans (EPM: 12,43 mm; EPV: 12,78 mm), Candida parapsilosis (EPM: 14,88 mm; EPV: 13,96 mm) e Cutaneotrichosporon dermatis (EPM: 11,95; EPV: 12,28 mm), foram as mais susceptíveis frente ambos os extratos. Pode-se inferir que os extratos possuem excelente atividade antifúngica, possivelmente associada ao rico conteúdo fenólico e de flavonoides.
Potencial antifúngico das própolis verde e marrom brasileiras contra leveduras clinicamente relevantes.
Keywords: Antifungal Activity; Candida spp. and yeast pathogens; Ethanolic Extract; Flavonoids; Propolis; Atividade Antifúngica; Candida spp. e leveduras patogênicas; Extrato Etanólico; Flavonoides; Própolis